(untitled) (Journal of Solar Energy Research Updates, 2021)
In this study, a validated computational simulation is presented to investigate the effect of humidity on the performance prediction of the solar vortex engine system. Data from an experimental model are used to validate the CFD simulation. Three humidity cases are considered: dry air, 40% and 80% humid air. An expansion process with heat addition is taking place inside the vortex generator. When the vortex field continues outside the system, a compression process with heat rejection occurs, eventually bringing the air vortex to be thermal and mechanical equilibrium with the surrounding atmosphere. The change in total energy and the heat transfer rate for both processes, inside the vortex generator and outside the vortex generator, increase with increased humidity in the working fluid. The humidity increases the energy required by the system to generate and maintain the air vortex. Compared to the dry air, the pressure drop at the center of the vortex field decreases by (2-5%) and (4-9%) for the 40% and 80% humid air, respectively. Reduced pressure drop decreases the stability of the air vortex when it is in contact with the atmosphere. The intensity of the air vortex is not affected by the increase in humidity.